Interfacial treatment-induced high-strength plant fiber/phenolic resin composite - Zhou, Shaoqian; Chen, Xueying; Huang, Rixin; Lin, Yi; Ye, Xiaoxia (Frontiers in Materials, 2022)
Plant straw fibers have been used widely in composite materials as reinforcement due to their advantages of low density, easy degradation, low cost, and abundance. However, the mechanical properties and water resistance of the as-prepared composites are limited due to the poor compatibility between plant straw fibers and polymer matrix. In this work, the rice straw fibers were pretreated with the silane coupling agent, lipase, and hydrothermal, and then blended with phenolic resin to prepare composites. The results showed that the pretreatment of the fibers can improve their compatibility with the resin matrix and improve the comprehensive mechanical properties and the thickness swelling of composites. When the mass ratio of fiber to resin is 1:1 and the hot-pressing condition is 160 °C and 11 min, the static bending strength, elastic modulus, and thickness swelling of the phenolic resin/lipase-treatment rice straw fibers (PF/L-SF) composite reached 23.03 MPa and 2588.39 MPa, which increased by 32.9% and 30.5% compared with the unmodified fiber/phenolic resin composite (PF/SF).